The Analysis of Learning Media in Islamic Religious Education: Definition, Functions, Principles, and Classification - Agus Susanto; Puput Fadila Layyina; Neneng Soliha Huzairiah; Naura Zakia Ramadhani (Cv. Kayaswara, Indonesia, 2025)
This study aims to analyze instructional media in Islamic Religious Education (IRE), focusing on its definition, functions, principles, and classification. A library research approach was employed to gather relevant literature and examine various types of media used in IRE. The findings indicate that instructional media in IRE serves not only as a technical aid but also as a tool for da’wah (Islamic preaching) and the transmission of values. The media helps accommodate diverse learning styles, particularly visual learning, through interactive formats. Key functions include capturing attention, increasing interest, facilitating understanding, and aiding students with learning difficulties. The effective use of media is guided by principles such as simplicity, clarity, and alignment with students' needs. Media utilization is also influenced by philosophical, psychological, empirical, and technological aspects. The study classifies media into three categories: audio, visual, and audiovisual, and emphasizes the need for innovative, value-based development to meet the demands of contemporary learners.